(untitled) (Vietnam Journal of Community Medicine, 2024)
Overview: A solitary pulmonary nodule (SPN) is a lesion measuring less than 3 cm, typically discovered incidentally through diagnostic imaging techniques. In recent years, low-dose computed tomography (LDCT) has become a popular screening method, particularly in lung cancer screening programs for high-risk groups. LDCT provides the capability for early detection of small lesions and significantly reduces radiation exposure compared to conventional CT, thereby mitigating negative impacts associated with radiation exposure. However, the management of solitary pulmonary nodules still faces many challenges, particularly in distinguishing between benign and malignant nodules. The management process is based on clinical evaluation, risk factors, and imaging characteristics of the nodule on LDCT. Clinical Case: A 70-year-old male patient with a history of smoking was found to have a solitary pulmonary nodule measuring 10 mm on LDCT during a lung cancer screening program. The nodule exhibited irregular margins and was asymptomatic. Based on risk factors and imaging characteristics, the patient was referred for a PET-CT scan to further assess malignancy. The PET-CT results indicated high metabolic activity in the nodule, suggesting a potential malignancy. Due to the location of the nodule, a biopsy under CT guidance was not feasible. The patient underwent thoracoscopic surgery for a cold biopsy, and the results confirmed early-stage lung cancer. Subsequently, the patient underwent a lower left lobectomy. The patient recovered well and was placed under regular follow-up. Conclusion: Low-dose computed tomography plays a crucial role in the early detection of solitary pulmonary nodules, thereby enhancing the efficacy of lung cancer screening and treatment. The management and treatment of pulmonary nodules require a combination of clinical risk factors, imaging studies, and invasive diagnostic methods when necessary. The monitoring and treatment process should be individualized based on each specific case to optimize treatment outcomes, ultimately improving patient survival rates.